The effectiveness of the non-standard policy measures during the financial crises: the experiences of the federal reserve and the European Central Bank - Seth Carpenter; Selva Demiralp; Jens Eisenschmidt (European Central Bank (ECB), 2013)
A growing number of studies have sought to measure the effects of non-standard policy on bank funding markets. The purpose of this paper is to carry those estimates a step further by looking at the effects of bank funding market stress on the volume of bank lending, using a simultaneous equation approach. By separately modeling loan supply and demand, we determine how nonstandard central bank measures affected bank lending by reducing stress in bank funding markets. We focus on the Federal Reserve and the European Central Bank. Our results suggest that non-standard policy measures lowered bank funding volatility. Lower bank funding volatility in turn increased loan supply in both regions, contributing to sustain lending activity. We consider this as strong evidence for a “bank liquidity risk channel”, operative in crisis environments, which complements the usual channels of transmission of monetary policy.
Keywords: E58; G32; G21; 330; bank funding volatility; bank lending; non-standard policy